2005
DOI: 10.1016/j.str.2005.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteomics: High-Throughput Structural and Functional Annotation of Proteins in Structural Genomics

Abstract: A high-throughput method for measuring transition metal content based on quantitation of X-ray fluorescence signals was used to analyze 654 proteins selected as targets by the New York Structural GenomiX Research Consortium. Over 10% showed the presence of transition metal atoms in stoichiometric amounts; these totals as well as the abundance distribution are similar to those of the Protein Data Bank. Bioinformatics analysis of the identified metalloproteins in most cases supported the metalloprotein annotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 42 publications
1
95
0
Order By: Relevance
“…In the crystal, substitution of Cd 2ϩ ions for the natural Zn 2ϩ binding sites has been observed. Similar substitutions from the crystallization buffers have been previously reported (19). In VP9, all the natural Zn 2ϩ binding sites might be taken up by the Cd this fact, the NMR titration experiments with various divalent metal ions were carried out.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In the crystal, substitution of Cd 2ϩ ions for the natural Zn 2ϩ binding sites has been observed. Similar substitutions from the crystallization buffers have been previously reported (19). In VP9, all the natural Zn 2ϩ binding sites might be taken up by the Cd this fact, the NMR titration experiments with various divalent metal ions were carried out.…”
Section: Resultssupporting
confidence: 58%
“…Since there is no histidine and only one cysteine is present in the sequence of VP9, the observed coordinating side chains could be considered an unconventional binding site for Zn 2ϩ . Recently, Shi et al (19) reported a similar unconventional Zn 2ϩ binding site with His, Asp, and Glu. VP9 has identical coordinating side chains, except that histidine is replaced by cysteine.…”
Section: Resultsmentioning
confidence: 97%
“…1). One caveat might be the lack of complete proteome annotation; 60 to 65% of a given proteome can be structurally characterized with the SUPERFAMILY HMMs, yet the structural genomics initiative suggests that the nonannotated portions of proteomes have a similar proportion of metal-binding domains (24).…”
Section: Resultsmentioning
confidence: 99%
“…Bertini et al proposed an approach taking advantage of known consensus sequences, i.e., taking into account the nature and spacing of amino acids present in the metal-binding region; the distribution of iron-, copper-, and zinc-binding proteins in several archaea, bacteria, and eukaryotes was thus described [65]. The bioinformatic analysis of the protein sequence (by correlation with the relevant gene) allows the finding of the conserved metal-binding motifs and provides important clues to function and metal site structure [68]. This approach is critically dependent on the availability of consensus sequences for the binding of different metals.…”
Section: Bioinformatics and Prediction Of The Metal-binding Patternsmentioning
confidence: 99%